Life Cycle Assessment of Metal Mailbox A case study - Zhang, Luxin (My University, 2023)
English
Keywords: life cycle analysis; emissions; product life cycle; environmental effects; greenhouse gases; evaluation; sustainable development; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management